ПРИМЕНЕНИЕ МЕТОДИКИ ECVET ДЛЯ ОПИСАНИЯ БЛОКА РЕЗУЛЬТАТОВ ОБУЧЕНИЯ «АРХИТЕКТУРА ПЕРСОНАЛЬНОГО КОМПЬЮТЕРА» - Турениязова, А.И. (SCIENCE and SOCIETY, 2019)
In the article an example of deseribing learning outcomes and assessment criteria on methodology of ECVET (European Credit System for Vocational Education and Training), learning outcomes and assessment eriteria for the Personal Computer Architecture Unit in speciality «Technician of computer engineering» is given.